2010
DOI: 10.1359/jbmr.091011
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fibronectin affects bone matrix, whereas osteoblast fibronectin modulates osteoblast function

Abstract: The bone matrix is composed mostly of collagen, but the initial and continuous presence of fibronectin was found to be crucial for collagen matrix integrity in vitro. It has been assumed that osteoblasts produce the fibronectin required for bone matrix formation. Using transgenic mice, we conditionally deleted fibronectin in the osteoblasts and in the liver using the cre-loxP system. We also used mice with mutated fibronectin and conditionally deleted b 1 -integrin in osteoblasts to identify the receptor invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 40 publications
4
89
0
2
Order By: Relevance
“…36,48,[66][67][68] Our work is the first to demonstrate that pFN, synthesized by hepatocytes in liver, contributes to adipogenesis. This adds to the list of tissues (liver, brain, testis, heart, lungs, and bone 37,38 ) and cell types that have been shown to accumulate pFN for their function. 32,33 Furthermore, although FN matrix is clearly an important component of WAT and preadipocyte cultures, its actual function has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,48,[66][67][68] Our work is the first to demonstrate that pFN, synthesized by hepatocytes in liver, contributes to adipogenesis. This adds to the list of tissues (liver, brain, testis, heart, lungs, and bone 37,38 ) and cell types that have been shown to accumulate pFN for their function. 32,33 Furthermore, although FN matrix is clearly an important component of WAT and preadipocyte cultures, its actual function has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In the physiological setting, FN exists as 2 pools: as cellular FN (cFN) synthesized by tissue-resident cells and as plasma FN (pFN) produced by the liver. 31 pFN has recently been shown to accumulate from the circulation into several tissues (liver, brain, testis, heart, lungs, and bone), 37,38 and to contribute to the majority of the FN extracellular matrix associated with several cell types. 16,[31][32][33] FXIII-A has been shown to increase FN matrix accumulation in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…62). Spontaneous metastasis of breast cancer to lung and bone is enhanced by α ν β 3 integrins, partially due to their strong binding to fibronectin and vitronectin (63)(64)(65). In addition, binding of α ν β 3 integrins to ECM proteins prevents apoptosis in a foreign environment (66).…”
Section: The Ecm Composition Arranges Motility and Invasionmentioning
confidence: 99%
“…37 Studies with a variety of different conditional knockout animals demonstrated that while osteoblasts produce fibronectin, they are not responsible for the presence of the same in the bone extracellular matrix; rather, the bone matrix fibronectin is derived from circulating liver fibronectin. 38 In primary biliary cirrhosis, the incidence of osteoporosis is markedly elevated. This higher incidence is due to an increased production of a fibronectin isoform that lessens osteoblastic bone formation.…”
Section: Bone Composition and Osteoporosis Al Boskeymentioning
confidence: 99%